2009
DOI: 10.1007/978-1-60761-416-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Multidrug Resistance in Cancer

Abstract: The development of multidrug resistance (MDR) to chemotherapy remains a major challenge in the treatment of cancer. Resistance exists against every effective anticancer drug and can develop by numerous mechanisms including decreased drug uptake, increased drug efflux, activation of detoxifying systems, activation of DNA repair mechanisms, evasion of drug-induced apoptosis, etc. In the first part of this chapter, we briefly summarize the current knowledge on individual cellular mechanisms responsible for MDR, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
468
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 604 publications
(479 citation statements)
references
References 216 publications
4
468
0
7
Order By: Relevance
“…Over the past 30 y, in vitro studies have led to the enumeration of close to 400 genes whose expression affects response to chemotherapy (13). Among those genes, ATP-binding cassette (ABC) transporters, a superfamily of 48 highly homologous members classified in seven subfamilies, have an important role in the pleiotropic mechanisms mediating MDR by exporting chemotherapeutic agents from the cell (14,15).…”
mentioning
confidence: 99%
“…Over the past 30 y, in vitro studies have led to the enumeration of close to 400 genes whose expression affects response to chemotherapy (13). Among those genes, ATP-binding cassette (ABC) transporters, a superfamily of 48 highly homologous members classified in seven subfamilies, have an important role in the pleiotropic mechanisms mediating MDR by exporting chemotherapeutic agents from the cell (14,15).…”
mentioning
confidence: 99%
“…It is suggested that different tumor cell types have their own unique mechanisms leading to MDR (Gillet and Gottesman, 2010;Al-Lazikani et al, 2012). The association between GST and tumors was initially reported by Wang (Wang and Few, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…Genetic and molecular studies have shown that most of the malignant cancer cells have amplified multi drug resistance (MDR) 1 and multidrug resistance associated protein (MRP) genes, which are the members of ATP-binding cassette transporter (ABC transporter) superfamily. 97 Now, a series of studies dictate that tumor derived exosomes added the layer of complexity in the complex nature of cancer by transmission of resistance from resistant cells to sensitive ones (Figure 1). Bebawy et al, showed the transmission of functional P-glycoprotein (P-gp) (MDR1) from drug resistant cancer cells (VLB 100 ) to drug sensitive cancer cells (CCRF-CEM) over a co-culture period of 4 hours.…”
Section: Role In Drug Resistancementioning
confidence: 99%